Pengetahuan dan Karakteristik Individu: Studi Cakupan Kepatuhan Minum Obat Paska Pemberian Obat Massal Pencegahan Filariasis di Kabupaten Tangerang - Heni Prasetyowati; Dewi Nur Hodijah; Mara Ipa; Joni Hendri (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Tangerang Regency as one of the endemic filariasis districts has completed provision of Mass Drug Administration (MDA) in five rounds from 2008 to 2012. The re-emergence of new cases after MDA needs to be monitored and evaluated, related to community compliance in taking preventive mass drugs as well as the knowledge and characteristics of influencing individuals. The aims of this study is to analyze the correlation of knowledge and characteristics of individuals with the participation and compliance of taking preventive filariasis drugs. The variables analyzed were individual characteristics which included gender, age, marital status, education level, type of work as well as knowledge variables. These variables were analyzed using a regression test. Based on the interview results of 660 respondents, only 54% of respondents claimed to have participated in the POPM program. Statistical analysis showed that gender, age of respondents and knowledge had a significant correlation to the participation of respondents in the filariasis treatment program. Of the 54% of respondents who participated in POPM filariasis, only 70% took all the drugs given. All variables tested did not have a significant relationship to the respondents' compliance in taking the received filariasis medication. Community participation in MDA is still below the specified target, as well as community compliance in taking drugs.